Tumor Necrosis Factor-α-Induced Protein 8-Like 2 Ameliorates Cardiac Hypertrophy by Targeting TLR4 in Macrophages - Rui Yao (Oxidative Medicine and Cellular Longevity, 2022)
Background. Tumor necrosis factor-α-induced protein 8-like 2 (TIPE2), a novel immunoregulatory protein, has been reported to regulate inflammation and apoptosis. The role of TIPE2 in cardiovascular disease, especially cardiac hypertrophy, has not been elucidated. Thus, the aim of the present study was to explore the role of TIPE2 in cardiac hypertrophy. Methods. Mice were subjected to aortic banding (AB) to induce an adverse hypertrophic model. To overexpress TIPE2, mice were injected with a lentiviral vector expressing TIPE2. Echocardiographic and hemodynamic analyses were used to evaluate cardiac function. Neonatal rat cardiomyocytes (NRCMs) and mouse peritoneal macrophages (MPMs) were isolated and stimulated with angiotensin II. NRCMs and MPM were also cocultured and stimulated with angiotensin II. Cells were transfected with Lenti-TIPE2 to overexpress TIPE2. Results. TIPE2 expression levels were downregulated in hypertrophic mouse hearts and in macrophages in heart tissue. TIPE2 overexpression attenuated pressure overload-induced cardiac hypertrophy, fibrosis, and cardiac dysfunction. Moreover, we found that TIPE2 overexpression in neonatal cardiomyocytes did not relieve the angiotensin II-induced hypertrophic response in vitro. Furthermore, TIPE2 overexpression downregulated TLR4 and NF-κB signaling in macrophages but not in cardiomyocytes, which led to diminished inflammation in macrophages and consequently reduced the activation of hypertrophic Akt signaling in cardiomyocytes. TLR4 inhibition by TAK-242 did not enhance the antihypertrophic effect of TIPE2 overexpression. Conclusions. The present study indicated that TIPE2 represses macrophage activation by targeting TLR4, subsequently inhibiting cardiac hypertrophy.